Functional Analyses of MMPs for Aragonite Crystal Formation in the Ligament of Pinctada fucata - Kubota, Kazuki; Kintsu, Hiroyuki; Matsuura, Akihiro; Tsuchihashi, Yasushi; Takeuchi, Takeshi; Satoh, Noriyuki; Suzuki, Michio (Frontiers in Marine Science, 2018)
The mollusk class, Bivalvia, plays an important role in the formation of calcium carbonate in the ocean. The bivalve hinge ligament is hard but pliant tissue that resists the stress placed on the hinge during opening and closing. The ligament comprises a fine microstructure of fibrous aragonite crystals surrounded by a dense organic matrix. The matrix consists of organic fibers that are aligned with the fibrous aragonite crystals. Previous studies identified a tissue inhibitor of metalloproteinase (Pf-TIMP) in the organic fibers of Pinctada fucata ligaments. This enzyme exhibited strong inhibition of matrix metalloproteinase (MMP) activity in vitro, suggesting that MMPs also play a role in formation of the organic fibers of the ligament. Using transcriptome data, we identified MMP genes from the mantle isthmus, which is a soft tissue attached to the ligament. To investigate the function of MMP genes in vivo, we performed RNA interference experiments. The expression of MMP14973 and MMP07860 genes was inhibited after injection of each dsRNA. Cumulative injection of MMP07860 dsRNA induced disordered aragonite fiber orientation, whereas the injection of MMP14973 had no effect. When the decalcified ligament was incubated in a solution saturated with calcium carbonate, aragonite fibers aligned along the surface. To investigate MMP function in calcium carbonate crystallization in detail, we precipitated aragonite crystals in collagen gels treated with or without recombinant MMP-1. Treatment with MMP-1 increased the interaction between collagen gels and calcium carbonate. These results suggest that MMPs degrade extracellular matrices in the ligament to produce the fine organic fibers that regulate the orientation of fibrous aragonite crystals.